Leadership development for orthopaedic trauma surgeons in Latin America: opportunities for and barriers to skill acquisition. Issue 4 (19th December 2021) - MacKechnie, Madeline C.; MacKechnie, Michael A.; Lieshout, Esther M.M. van; Verhofstad, Michael H.J.; Quintero, Jose Eduardo; Padilla Rojas, Luis G.; Tabares Neyra, Horacio; Russo, Bibiana Dello; Giordano, Vincenzo; Vilensky, Eduardo; Fuehrer, Sheryl L.; Miclau, Theodore
Abstract : Supplemental Digital Content is available in the text Abstract: Introduction: There is growing interest in leadership courses for physicians. Few opportunities are available in global regions with limited resources. This study describes orthopaedic trauma surgeons' desired leadership skill acquisition, opportunities, and barriers to course participation in Latin America. Methods: Latin American orthopaedic trauma surgeons from the Asociación de Cirujanos Traumatólogos de las Americas (ACTUAR) network were surveyed. This survey solicited and gauged the surgeons' level of interest in leadership topics and their relative importance utilizing a 5-point Likert-scale. Additionally, comparisons were calculated between middle-income countries (MICs) and high-income countries (HICs) to ascertain if needs were different between groups. The survey included demographic information, nationality, level of training, years in practice, leadership position, needs assessment, and perceived barriers for leadership educational opportunities. Results: One hundred forty-four orthopaedic surgeons completed the survey, representing 18 countries across Latin America; 15 MICs and 3 HICs. Participants had more than 20 years in practice (49%) and held leadership positions (81%) in hospital settings (62%), national orthopaedic societies (45%), and/or clinical settings (40%). Sixty-three percent had never attended a leadership course due to lack of opportunities/invitations (69%), difficulty missing work (24%), and costs (21%). Ninety-seven percent expressed interest in attending a leadership course. No difference in needs was determined between respondents from MICs and HICs. Professional Ethics, Crisis Management/Organizational Change Management, and High Performing Team-Building were identified as the most important leadership topics. Conclusion: Orthopaedic surgeons in Latin America demonstrate an interest in acquiring additional leadership skills but have few opportunities. Identifying interests, knowledge gaps, and core competencies can guide the development of such opportunities.